Surgical treatment of syphilitic superficial femoral artery aneurysm: a rare case report. Issue 1 (December 2015) - Cheng, Zhihua; Luo, Sean; Sun, Xiwei; Sun, Siqiao; Wang, Zhongying; Jiang, Yuzhu; An, Zhiyuan; Wang, Qi
Abstract Background Arterial aneurysm is a known complication of syphilis, but the occurrence of femoral artery aneurysm secondary to the syphilitic disease has never been reported. Case presentation The present study described a 60-year-old Chinese male who presented with two aneurysms in the middle and lower segment of the right superficial femoral artery causing the symptoms of pain, coldness and numbness in the right lower limb. This case was diagnosed with syphilitic superficial femoral aneurysm because of positive syphilitic testing and the inflammatory cell infiltration around the adventitial vasa vasorum under the pathological examination. Anti-syphilis treatment, stent graft implantation and open surgery were attempted to eliminate the syphilis and aneurysm, which was ultimately successful, with no symptoms after a follow-up of 3 months. Conclusion Combined open and endovascular repair may be effective and safe for treatment of syphilitic femoral artery aneurysms.